(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
In this study, a mixed-method research approach is used to examine how task-based language teaching (TBLT) affects the English language ability of different learners. A total of 120 participants’ intermediate, advanced, and adult learners came from three different academic institutions for the research. In addition to structured questionnaires assessing motivation and engagement levels, pre- and post-test evaluations of speaking, listening, reading, and writing abilities were used to gather quantitative data. Classroom observations and semi-structured interviews were used to get qualitative insights. The findings showed that after the intervention, all language skills significantly improved, and that TBLT increased participant motivation and involvement. Authentic communication and enhanced learner confidence were among the major themes that emerged from the qualitative research. Teachers should include task-based learning into their curricula, since the results demonstrate how well TBLT fosters language competency and student engagement. Future studies investigating the long-term impacts of TBLT in various settings are advised.